Dizziness post chiropractic manipulation of spine-a case report - Devaraj, Navin Kumar (Fortune Journals, 2019)
In recent years, chiropractic therapy over the spine has become a popular alternative treatment for headache, neck pain and backache. While not denying its effects in a selected group of patients, it also has its inherent list of side effects. This case report looks at a 72-years-old woman who complained of dizziness for three days after undergoing continuous chiropractic spinal manipulation therapy for her chronic back pain for two weeks.